src/HOL/Algebra/Module.thy
 author ballarin Mon, 05 May 2003 10:53:27 +0200 changeset 13952 6206d3e7672a parent 13949 0ce528cd6f19 child 13975 c8e9a89883ce permissions -rw-r--r--
Fixed but with old versions of pdflatex (fancy symbols not allowed in bookmarks).
```
(*  Title:      HOL/Algebra/Module
ID:         \$Id\$
Author:     Clemens Ballarin, started 15 April 2003
*)

theory Module = CRing:

section {* Modules over an Abelian Group *}

record ('a, 'b) module = "'b ring" +
smult :: "['a, 'b] => 'b" (infixl "\<odot>\<index>" 70)

locale module = cring R + abelian_group M +
assumes smult_closed [simp, intro]:
"[| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^sub>2 x \<in> carrier M"
and smult_l_distr:
"[| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<oplus> b) \<odot>\<^sub>2 x = a \<odot>\<^sub>2 x \<oplus>\<^sub>2 b \<odot>\<^sub>2 x"
and smult_r_distr:
"[| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
a \<odot>\<^sub>2 (x \<oplus>\<^sub>2 y) = a \<odot>\<^sub>2 x \<oplus>\<^sub>2 a \<odot>\<^sub>2 y"
and smult_assoc1:
"[| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<otimes> b) \<odot>\<^sub>2 x = a \<odot>\<^sub>2 (b \<odot>\<^sub>2 x)"
and smult_one [simp]:
"x \<in> carrier M ==> \<one> \<odot>\<^sub>2 x = x"

locale algebra = module R M + cring M +
assumes smult_assoc2:
"[| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
(a \<odot>\<^sub>2 x) \<otimes>\<^sub>2 y = a \<odot>\<^sub>2 (x \<otimes>\<^sub>2 y)"

lemma moduleI:
assumes cring: "cring R"
and abelian_group: "abelian_group M"
and smult_closed:
"!!a x. [| a \<in> carrier R; x \<in> carrier M |] ==> smult M a x \<in> carrier M"
and smult_l_distr:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
smult M (add R a b) x = add M (smult M a x) (smult M b x)"
and smult_r_distr:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
smult M a (add M x y) = add M (smult M a x) (smult M a y)"
and smult_assoc1:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
smult M (mult R a b) x = smult M a (smult M b x)"
and smult_one:
"!!x. x \<in> carrier M ==> smult M (one R) x = x"
shows "module R M"
by (auto intro: module.intro cring.axioms abelian_group.axioms
module_axioms.intro prems)

lemma algebraI:
assumes R_cring: "cring R"
and M_cring: "cring M"
and smult_closed:
"!!a x. [| a \<in> carrier R; x \<in> carrier M |] ==> smult M a x \<in> carrier M"
and smult_l_distr:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
smult M (add R a b) x = add M (smult M a x) (smult M b x)"
and smult_r_distr:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
smult M a (add M x y) = add M (smult M a x) (smult M a y)"
and smult_assoc1:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
smult M (mult R a b) x = smult M a (smult M b x)"
and smult_one:
"!!x. x \<in> carrier M ==> smult M (one R) x = x"
and smult_assoc2:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
mult M (smult M a x) y = smult M a (mult M x y)"
shows "algebra R M"
by (auto intro!: algebra.intro algebra_axioms.intro cring.axioms
module_axioms.intro prems)

lemma (in algebra) R_cring:
"cring R"
by (rule cring.intro) assumption+

lemma (in algebra) M_cring:
"cring M"
by (rule cring.intro) assumption+

lemma (in algebra) module:
"module R M"
by (auto intro: moduleI R_cring is_abelian_group
smult_l_distr smult_r_distr smult_assoc1)

subsection {* Basic Properties of Algebras *}

lemma (in algebra) smult_l_null [simp]:
"x \<in> carrier M ==> \<zero> \<odot>\<^sub>2 x = \<zero>\<^sub>2"
proof -
assume M: "x \<in> carrier M"
note facts = M smult_closed
from facts have "\<zero> \<odot>\<^sub>2 x = (\<zero> \<odot>\<^sub>2 x \<oplus>\<^sub>2 \<zero> \<odot>\<^sub>2 x) \<oplus>\<^sub>2 \<ominus>\<^sub>2 (\<zero> \<odot>\<^sub>2 x)" by algebra
also from M have "... = (\<zero> \<oplus> \<zero>) \<odot>\<^sub>2 x \<oplus>\<^sub>2 \<ominus>\<^sub>2 (\<zero> \<odot>\<^sub>2 x)"
by (simp add: smult_l_distr del: R.l_zero R.r_zero)
also from facts have "... = \<zero>\<^sub>2" by algebra
finally show ?thesis .
qed

lemma (in algebra) smult_r_null [simp]:
"a \<in> carrier R ==> a \<odot>\<^sub>2 \<zero>\<^sub>2 = \<zero>\<^sub>2";
proof -
assume R: "a \<in> carrier R"
note facts = R smult_closed
from facts have "a \<odot>\<^sub>2 \<zero>\<^sub>2 = (a \<odot>\<^sub>2 \<zero>\<^sub>2 \<oplus>\<^sub>2 a \<odot>\<^sub>2 \<zero>\<^sub>2) \<oplus>\<^sub>2 \<ominus>\<^sub>2 (a \<odot>\<^sub>2 \<zero>\<^sub>2)"
by algebra
also from R have "... = a \<odot>\<^sub>2 (\<zero>\<^sub>2 \<oplus>\<^sub>2 \<zero>\<^sub>2) \<oplus>\<^sub>2 \<ominus>\<^sub>2 (a \<odot>\<^sub>2 \<zero>\<^sub>2)"
by (simp add: smult_r_distr del: M.l_zero M.r_zero)
also from facts have "... = \<zero>\<^sub>2" by algebra
finally show ?thesis .
qed

lemma (in algebra) smult_l_minus:
"[| a \<in> carrier R; x \<in> carrier M |] ==> (\<ominus>a) \<odot>\<^sub>2 x = \<ominus>\<^sub>2 (a \<odot>\<^sub>2 x)"
proof -
assume RM: "a \<in> carrier R" "x \<in> carrier M"
note facts = RM smult_closed
from facts have "(\<ominus>a) \<odot>\<^sub>2 x = (\<ominus>a \<odot>\<^sub>2 x \<oplus>\<^sub>2 a \<odot>\<^sub>2 x) \<oplus>\<^sub>2 \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)" by algebra
also from RM have "... = (\<ominus>a \<oplus> a) \<odot>\<^sub>2 x \<oplus>\<^sub>2 \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)"
also from facts smult_l_null have "... = \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)" by algebra
finally show ?thesis .
qed

lemma (in algebra) smult_r_minus:
"[| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^sub>2 (\<ominus>\<^sub>2x) = \<ominus>\<^sub>2 (a \<odot>\<^sub>2 x)"
proof -
assume RM: "a \<in> carrier R" "x \<in> carrier M"
note facts = RM smult_closed
from facts have "a \<odot>\<^sub>2 (\<ominus>\<^sub>2x) = (a \<odot>\<^sub>2 \<ominus>\<^sub>2x \<oplus>\<^sub>2 a \<odot>\<^sub>2 x) \<oplus>\<^sub>2 \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)"
by algebra
also from RM have "... = a \<odot>\<^sub>2 (\<ominus>\<^sub>2x \<oplus>\<^sub>2 x) \<oplus>\<^sub>2 \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)"
also from facts smult_r_null have "... = \<ominus>\<^sub>2(a \<odot>\<^sub>2 x)" by algebra
finally show ?thesis .
qed

subsection {* Every Abelian Group is a Z-module *}

(* Not all versions of pdflatex permit \$\mathbb{Z}\$ in bookmarks. *)

text {* Not finished. *}

constdefs
INTEG :: "int ring"
"INTEG == (| carrier = UNIV, mult = op *, one = 1, zero = 0, add = op + |)"

(*
INTEG_MODULE :: "('a, 'm) ring_scheme => (int, 'a) module"
"INTEG_MODULE R == (| carrier = carrier R, mult = mult R, one = one R,
zero = zero R, add = add R, smult = (%n. %x:carrier R. ... ) |)"
*)

lemma cring_INTEG:
"cring INTEG"
by (unfold INTEG_def) (auto intro!: cringI abelian_groupI comm_monoidI